2009
DOI: 10.1200/jco.2009.22.1135
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D3 Levels Are Associated With Breslow Thickness at Presentation and Survival From Melanoma

Abstract: Results from the retrospective study were consistent with a role for vitamin D in melanoma outcome. The cohort study tests this hypothesis, providing evidence that higher 25-hydroxyvitamin D(3) levels, at diagnosis, are associated with both thinner tumors and better survival from melanoma, independent of Breslow thickness. Patients with melanoma, and those at high risk of melanoma, should seek to ensure vitamin D sufficiency. Additional studies are needed to establish optimal serum levels for patients with mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
267
4
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(313 citation statements)
references
References 28 publications
25
267
4
12
Order By: Relevance
“…Of the two studies [10,16] that assessed both vitD and VDR, only one [16] explored their prognostic interaction. However, the prognostic significance of several VDR polymorphisms was limited to patients with very low serum vitD levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the two studies [10,16] that assessed both vitD and VDR, only one [16] explored their prognostic interaction. However, the prognostic significance of several VDR polymorphisms was limited to patients with very low serum vitD levels.…”
Section: Discussionmentioning
confidence: 99%
“…In one of them [25], A-1012G (A allele) (AA genotype), but not the Fok1 and Taq1 polymorphisms, was associated with a greater risk for metastasis than the GG/AG genotype (HR, 2.9; 95% CI, 1.1-7.5). In the second study [16], there was no clear effect of several VDR polymorphisms on outcome, apart from weak evidence that inheritance of the Bsm1 A allele was adversely associated with RFS (HR, 1.44; 95% CI, 1.02-2.03). However, stratifying patients according to vitD status, inheritance of the Bsm1 A, Apa1 A, and Taq1 C alleles was associated with a higher risk for relapse from melanoma in patients with low vitD levels, but not in those with normal/elevated vitD levels (interaction test, p ϭ .02).…”
Section: Vdr Expression and Relevant Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from the UK measured serum vitamin D at diagnosis and found that those with the highest level of serum vitamin D had the best survival [181].…”
Section: Analytic Studiesmentioning
confidence: 99%
“…There remains controversy regarding the optimal level of serum vitamin D with respect to bone health, cancer, and wellness. A prospective cohort study suggested that vitamin D (serum 25-hydroxy-vitamin D3) levels are associated with lower Breslow thickness of melanoma at the time of diagnosis, as well as being protective of survival in terms of melanoma relapse and death independent of melanoma thickness (Newton-Bishop et al, 2009). However, at this time, there are no data to indicate that supplementation with vitamin D after diagnosis is protective for melanoma (Hutchinson et al, 2010).…”
Section: External Factors and Melanoma Risk Modificationmentioning
confidence: 84%